Predicting The Malaysian Gross Domestic Product Using Sliding Window Technique - Khoh, Irene Foong Lean (2008)
In Malaysia, the quarterly economic growth is announced two months after the end of every quarter. Market players, who need to know the future behaviour of economic growth before making important business decisions, would therefore need to forecast the growth rather than waiting for the announcements all the time. However, conventional forecasting methods have flaws as the margin of error is not within the acceptable error margin. This study aims to discover patterns of the Malaysian GDP growth using sliding window technique. Discovered patterns were tested and the forecasting results are promising.